Design of 2D Animation as an Educational Introduction to Butterfly Species for Children - Nada Salsabila; Pratama Bayu Widagdo (Gorga : Jurnal Seni Rupa, 2025)
Animation is essentially a field of study that combines elements of art and technology. In the world of education in the digital era, animation is widely used as a medium or tool for educating learners (children) because it is considered more engaging in delivering information audiovisually compared to media such as books. On the other hand, while knowledge of technology among children continues to increase, their understanding of biodiversity has significantly declined. One example is their awareness of butterfly diversity, even though butterflies play a vital role in the ecosystem. This research aims to design a 2-dimensional (2D) animation that functions as an educational medium to introduce various types of butterflies to children. The animation is expected to present information in an engaging way, thereby capturing children’s interest in learning about biodiversity, especially butterflies. This study uses an animation design method. The project follows a prototype-based development process consisting of design conceptualization and animation production stages. The result of this research is a 2-dimensional (2D) animation titled “Bulan and the Butterflies”, which tells the story of Bulan, a young girl, and a small fairy on a journey to learn about different types of butterflies, particularly those found in Indonesia and rare protected species. The conclusion derived from this study is that this 2D animation can serve as an educational tool capable of broadening children’s knowledge about butterflies and fostering their enthusiasm for environmental conservation. It can also encourage children’s interest in science, insects, and nature from an early age, while strengthening environmental awareness through visual media that is entertaining, educational, enjoyable, and inspiring.